Predictors of late presentation and advanced HIV disease among people living with HIV in Oman (2000-2019) - Ali Elgalib; Samir Shah; Adil Al-Wahaibi; Zeyana Al-Habsi; Maha Al-Fouri; Richard Lau; Hanan Al-Kindi; Bader Al-Rawahi; Seif Al-Abri (BMC, 2021)
Abstract Background The aim of this study was to determine the proportions and predictors of late presentation (LP) and advanced HIV disease (AD) in Oman. LP and AD were defined as presenting with a baseline CD4 count of < 350 and < 200 cells/mm3, respectively. Methods We conducted a retrospective database analysis of the National HIV Surveillance System to identify Omani people (≥ 13 years old) who were diagnosed with HIV in the period between January 2000 and December 2019 and had a documented baseline CD4 cell count. We calculated the rates and trend over time of LP and AD. A logistic regression was carried out to determine the predictors of LP and AD. Results A total of 1418 patients, who were diagnosed with HIV in the period from January 2000 to December 2019, were included; 71% were male and 66% were heterosexuals. The median (IQR) age at diagnosis was 33 (25-39) years. Overall, 71% (95% CI: 68-73) and 46% (95% CI: 44-49) of patients had LP and AD at presentation, respectively. The LP percentage decreased from 76% in 2000-2004 to 69% in 2015-2019; AD percentage decreased from 57 to 46% over the same period. The proportions of men with LP and AD were higher than women (74% vs. 62 and 50% vs. 36%, respectively). The percentages of persons with LP among people aged 13-24, 25-49, and ≥ 50 years were 65, 71, and 84%, respectively. The proportions of persons with AD among people aged 13-24, 25-49, and ≥ 50 years were 39, 46, and 65%, respectively. Logistic regression showed that male sex, older age, having an "unknown" HIV risk factor, and living outside Muscat were independent predictors of AD. Male sex also independently predicted LP. Conclusions This analysis indicates that a significant proportion of new HIV cases in Oman continue to present late. This study identified patient subgroups at greatest risk of late HIV diagnosis such as men and older people. Targeted interventions and greater efforts to scale up HIV testing services in Oman are needed.